Analysis of Students’ Creative Thinking in Science Learning - Ratna Dila Cahyaningsih; Agung Purwanto; Khaerudin Khaerudin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
In the current era, students face very complex problems in life. They can solve these problems depending on the ability to think creatively. The purpose of the research carried out was to determine the creative thinking skills of elementary school students in science learning on the water cycle material. The subjects of this study were 32 students in class V at an elementary school, in Kramatmulya District, Kuningan Regency, West Java Province. Data collection techniques carried out by using interviews and tests. The data analysis technique used is a qualitative descriptive analysis. The results of the study show that the average score associated with students' creative thinking is only about 34%. In addition, based on the results of interviews and tests, it shows that students' creative thinking is still low. The conclusion in this study is that students still have low creative thinking skills because scores on each indicator of creative thinking skills are still low.